Small Bowel Perforation Caused by Pancreaticojejunal Anastomotic Stent Migration after Pancreaticoduodenectomy for Periampullary Carcinoma - Mari, Giulio; Costanzi, Andrea; Monzio, Nicola; Miranda, Angelo; Rigamonti, Luca; Crippa, Jacopo; Sartori, Paola; Maggioni, Dario (JOP. Journal of the Pancreas, 2015)
Context Pancreaticoduodenectomy is the gold standard for patients with resectable periampullary carcinoma. The protection of the anastomosis by positioning of an intraluminal stent is a technique used to lower the frequency of anastomotic fistulas. However the use of anastomotic stents is still debated and stent related complications are reported. Case report A fifty-three-year old male underwent pancreaticoduodenectomy (PD) for a T2N0 periampullary carcinoma with a pancreaticojejunal (duct to mucosa) anastomosis protected by a free floating 6 Fr Nelaton stent in the Wirsung duct. Twenty-three months after surgery the patient accessed Emergency Department for severe abdominal pain associated to temperature, high white blood cell count and an significant increase in C reactive protein. Method Abdominal CT scan shown the presence of a tubular stent in the mesogastrium/lower right quadrant. No evident free intra-abdominal air was detected. The patient was submitted to explorative laparotomy. After debridement for localized peritonitis the Nelaton trans anastomotic stent was found in the abdomen. There was no evidence of bowel perforation, but intestinal loops covered with fibrin and suspect for impending perforation were resected. Conclusion There is a lack of evidence about the true rate of post-operative complications related to pancreatic stenting. We believe that in patients presenting with abdominal pain or peritonitis that previously underwent PD with stent-guided pancreaticojejunal anastomosis, the hypothesis of stent migration should at least be taken into consideration. Image: Decubitus sign of the stent.